Comparing the 7th and 8th Editions of AJCC Staging System for Hypopharyngeal Cancer Undergoing Surgery - Lin, Heng-Yu Haley; Chang, Chia-Fan; Lee, Tsung-Lun; Hsu, Yen-Bin; Tai, Shyh-Kuan; Yang, Muh-Hwa; Wang, Ling-Wei; Chu, Pen-Yuan (Otolaryngology-head and neck surgery, 2025)
The prognostic accuracy of the American Joint Committee on Cancer (AJCC) 8th staging system for hypopharyngeal cancer remains uncertain. We aim to assess its survival prediction accuracy and compare it with the 7th edition. Retrospective investigation of prospective data. Single-institution tertiary referral center. A cohort of 200 patients with hypopharyngeal squamous cell carcinoma who underwent surgical intervention as primary treatment between 2007 and 2019 was analyzed. We evaluated overall survival (OS) and disease-specific survival (DSS) using the Kaplan-Meier method and the log-rank test for each AJCC edition. The Akaike information criterion (AIC) was used to assess prognostic prediction performance. The median follow-up was 67 months (29-100 months). In total, 93% of the patients (N = 186) underwent at least one side of neck dissection. In total, 41% of patients (N = 82) were upstaged as per the AJCC 8th, all resulting from the redistribution of N stage. Survival curves for DSS were better distinguished for stages I, II, and IVb in the AJCC 8th edition, yet an overlap was observed between stages III and IVa. The combination of extranodal extension (ENE) and cervical metastasis level well-differentiated the survival curves for OS and DSS. The AJCC 8th system outperformed the 7th, with lower AIC values for OS (1092 vs 1098) and DSS (654 vs 666). The AJCC 8th edition improves survival prediction in hypopharyngeal cancer compared to the 7th, especially with the inclusion of ENE status and nodal metastasis classification revisions.